Analysis of Calculation of Cost of Production Based on Orders by the Full Costing Method on the CV. Citra Karya Media - Novelia Asita Mranani; Siwidyah Desi Lastianti; Yanna Eka Pratiwi (Journal of Economy, Accounting and Management Science (JEAMS), 2019)
This study aims to analyze the calculation of production costs in determining product prices by CV. Citra Karya Media with the full costing method. The problem in this study is "What is the cost of production in determining the price of goods sold in refrigerator products that meet all elements using the full costing method in CV Citra Karya Media? This calculation aims to determine the cost of goods manufactured Cabinets calculation calculated by CV Citra Karya Media by using the full costing method Types of data used are quantitative and qualitative data Data sources used are primary data and secondary data data collection techniques using interviews, documentation, and observation.The analysis method used is descriptive analysis.This results indicate that the costs are not calculated by the company in accordance with the full cost theory, some costs that are not calculated by the company such as indirect labor costs, electricity costs, property taxes, and building depreciation.Therefore it is important for the management of CV. make the right decision.